Analysis of the Energy Band Gap of Tin Oxide Thin Layers as Semiconductor Base Materials in Electronic Devices - Aris Doyan; Susilawati Susilawati; Lalu Muliyadi (Postgraduate, University of Mataram, 2022)
The purpose of this study is to analyze the quality of optical properties such as energy band gap of thin layer of tin oxide doped with aluminum, tin oxide doped with fluorine, tin oxide doped with indium, tin oxide doped with aluminum-fluorine, tin oxide doped with aluminum-indium, and tin oxide doped with aluminum-fluorine-indium. The thin layer was synthesized using the sol-gel spin coating method. The ratio of basic ingredients and doping used in this study was 95:5% and 85:15%. The thin layer that has been formed is then heated at a temperature of 100 and 200 0C. The results of the analysis of optical properties showed that the largest values of direct and indirect energy band gap are in a thin layer of tin oxide doped with indium at a percentage of 95:5% for a temperature of 100 0C, namely 3.62 and 3.92 eV. The lowest values of direct and indirect energy band gap are in a thin layer of tin oxide doped with aluminum-fluorine-indium at a percentage of 85:15% for a temperature of 200 0C, namely 3.36 and 3.51 eV. These results indicate that the resulting energy band gap decreases with increasing doping concentration and sintering temperature. Based on the optical properties obtained, the thin layer can be used as the basic material for semiconductors in electronic devices.